2007
DOI: 10.1097/mpg.0b013e31810e76a5
|View full text |Cite
|
Sign up to set email alerts
|

Iron Deficiency Among Children of Asylum Seekers in The Netherlands

Abstract: Iron deficiency is highly prevalent among the children of asylum seekers in the Netherlands. Our data indicate that systematic biochemical screening for ID is warranted in asylum seekers' children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 30 publications
2
3
0
2
Order By: Relevance
“…Iron deficiency anaemia was observed to be more prevalent among the age group 13-23months compared to the other age groups. This is in consonance with the findings of previous researchers 22,23 , who reported that severe iron deficiency anaemia usually affects children during their second year of life. attributed to increased iron requirements related to rapid growth in this age group.…”
Section: Discussionsupporting
confidence: 93%
“…Iron deficiency anaemia was observed to be more prevalent among the age group 13-23months compared to the other age groups. This is in consonance with the findings of previous researchers 22,23 , who reported that severe iron deficiency anaemia usually affects children during their second year of life. attributed to increased iron requirements related to rapid growth in this age group.…”
Section: Discussionsupporting
confidence: 93%
“…The possible consequences of untreated dental disease are significant. 12,13 The prevalence of IDA (22.1%) and IDA associated with a haemoglobinopathy and thalassaemia trait were similar to data from a small Dutch study 14 and more recent Australian data. 15 One hundred twelve children (10.9%) had a haemoglobinopathy or thalassaemia trait, but counselling for asymptomatic carriers is problematic as traits become clinically relevant only when children are of child-bearing age.…”
Section: Discussionsupporting
confidence: 79%
“…Issues related to obesity and overweight have appeared upon resettlement of AMC in host countries including the United States, the Netherlands, and Australia [80][81][82][83]. Some authors attribute these health issues to cigarette smoking [84] and changes to traditional lifestyle [81].…”
Section: Nutritionmentioning
confidence: 99%